2010
DOI: 10.1007/s11746-010-1597-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Color and Growing Locations on Fatty Acid Content and Composition of Two Chia (Salvia hispanica L.) Genotypes

Abstract: The objective of this study was to investigate the effect of chia (Salvia hispanica L.) seed coat color on oil content and fatty acid composition, as well as the effect of different growing areas on chemical variation. This study was carried out using white and black-spotted chia seeds grown together at five locations of Ecuador. Oil content was not significantly (P \ 0.05) different for any of the comparative analyses performed between white and black-spotted seeds at all, although significant differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
67
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 17 publications
15
67
3
3
Order By: Relevance
“…Evaluating the effect of different growing areas on the fatty acid composition of chia seed, Ayerza (2010) obtained LNA contents ranging from 61.06 to 66.75%, which differ from the values found in this study. Differences in fatty acid composition in chia seeds can be attributed to differences in environmental conditions such as temperature, light, soil type, nutrient availability (PEIRETTI; GAI, 2009), location (AYERZA, 2010), and the ecosystem where they are grown (AYERZA; COATES, 2011).…”
Section: Antioxidant Capacitycontrasting
confidence: 99%
See 2 more Smart Citations
“…Evaluating the effect of different growing areas on the fatty acid composition of chia seed, Ayerza (2010) obtained LNA contents ranging from 61.06 to 66.75%, which differ from the values found in this study. Differences in fatty acid composition in chia seeds can be attributed to differences in environmental conditions such as temperature, light, soil type, nutrient availability (PEIRETTI; GAI, 2009), location (AYERZA, 2010), and the ecosystem where they are grown (AYERZA; COATES, 2011).…”
Section: Antioxidant Capacitycontrasting
confidence: 99%
“…These results were similar to those found by Ciftci, Roman and Rudzinska (2012) for chia, perilla, and flax seeds, while Ayerza (2010) found lower rates for chia (from 0.23 to 0.32) than those reported in this study. The ratios obtained for perilla seeds were close to 0.23 (KIM; PARK; CHOUNG, 2007) and 0.25 (ECKERT; FRANKE; NOLDNER, 2010), values found in other studies.…”
Section: Antioxidant Capacitysupporting
confidence: 93%
See 1 more Smart Citation
“…tions. In this respect, Ayerza [43] established the existence of an inverse relationship between altitude and the content of saturated fatty acids (SFA); at low elevation, an increase in fatty acid saturation was noted in areas where the temperature was high. In Argentina, Ayerza [7] demonstrated that temperature largely contributed to the type of fatty acid found in the oil.…”
Section: Physicochemical Characterization Of Chia Oilmentioning
confidence: 99%
“…Reports on agronomic management of chia are only just starting to appear in the scientific literature; most of them are based on experiments and observations conducted in the areas of origin of South and Central America and focus mainly on the response of different genotypes to growing environments in terms of phenology, yield, and quality of seeds (Ayerza and Coates 2009a, b;Ayerza 1995Ayerza , 2010Ayerza , 2011Ayerza , 2013Lobo Zavalia et al 2011). Ongoing research in Basilicata, Southern Italy (Fig.…”
Section: Agronomic Managementmentioning
confidence: 99%